Perancangan Sistem Hotspot Manajemen Berbasis Voucher Menggunakan Mikrotik Pada Jaringan Rt/Rw Net Di Era Pandemi Covid-19 - yovan sakti; Maidel Fani (Politeknik Negeri Batam, 2022)
The spread of the Covid-19 virus at this time, which has reached the level of apandemic, has had a huge impact on many sectors, and one of them is theeducation sector. All students starting from elementary, middle, high school,and also the Batam College itself turned into online study through mediaconference. Therefore, it is necessary to have adequate and cost-effectiveinternet access, to assist the smooth process of learning and teaching. One ofthem is the need for cheap internet access that can reach the homes of residentswho have students, and also cheap. For this reason, in this final project, wewill design a Voucher-Based Hotspot Management System Using Mikrotik onan Rt/Rw-Net Network in the Covid-19 Pandemic Era. In this final project, theresearch method used is qualitative research. Respondents in this study werelocal residents in the Villamas housing RT 02, and the final result of thisresearch is a hotspot system that will be used by working officer and localstudents to be able to access the internet for online learning purposes.